Analisis Keamanan Jaringan Hardware Trojan Pada IoT - Dwi Suryono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Hardware Trojan is one of the attacks on Internet of Things (IoT) security which includes attacks on Radio Frequency Identification (RFID) labels, communication networks and data privacy. The purpose of this research is to describe the security of the Trojan Hardware network on the LoT with a literature review design or literature review. Miles and Huberman model data analysis is used in data analysis. As a result, IoT devices cannot be completely secure until we lay a solid hardware security foundation for them. All the effort and expense that goes into securing the device can be wasted if the device has a Hardware Trojan. Hardware security embedded in IoT is the need to protect the “identity” of devices to protect them against intrusion, and to protect the privacy and security of the data they generate. The use of Side-Channel Analysis provides another layer of security around key cryptography that is used to protect the integrity, confidentiality, and authenticity of systems and data.